The Effect of Digital Literacy on Self-Regulated Learning among Students in the Library and Information Science Program at Universitas Negeri Padang - Amelia, Preity; Desriyeni, Desriyeni (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid expansion of information technology has transformed students’ learning environments, requiring not only the ability to access digital information but also the capacity to regulate learning independently. However, the relationship between digital literacy and self-regulated learning in higher education remains insufficiently examined, particularly among Library and Information Science students. This study aims to identify the levels of digital literacy and self-regulated learning and to examine the effect of digital literacy on self-regulated learning among students of the Library and Information Science Program at Universitas Negeri Padang. A quantitative approach was employed, involving a population of 259 students, from which 72 respondents were selected through stratified proportional sampling. Data were collected using a structured questionnaire based on validated indicators and analyzed using simple linear regression. The findings show that both digital literacy and self-regulated learning are at a high level. The regression results indicate that digital literacy has a positive and statistically significant effect on self-regulated learning (Y = 11.107 + 0.670X; p < .05), with a coefficient of determination (R²) of 0.378, indicating that digital literacy explains 37.8% of the variance in self-regulated learning. These findings demonstrate that digital literacy plays an important role in enhancing students’ ability to plan, monitor, and evaluate their learning processes. This study contributes to the literature on digital learning and information science by providing empirical evidence of the relationship between digital literacy and self-regulated learning. Practically, the findings imply that strengthening digital literacy through curriculum integration and instructional strategies is essential to support autonomous learning and improve the quality of higher education.